A Study on the Impact of the Saudi Citizen Account as a Compensation Program to Achieve Food Security for Low-Income Citizens Under the Kingdom’s Vision 2030 - Althawaini, Heba; Elmulthum, Nagat; Morsi, Hafsa (Asian Development Policy Review, 2022)
This research aims to assess Saudi Citizen Account’s (CA) impact on low- and middle-income individuals by considering costs from increasing energy and water prices, and taxes imposed in Saudi Arabia. The minimum total household consumption expenditure was estimated (before and after the Saudi Vision 2030 economic reforms). The research covers all the expenditure groups in the Household Income and Expenditure Survey conducted by the General Authority for Statistics and estimates the linear expenditure system (LES) using the seemingly unrelated regressions (SUR) method. Results indicate variations in expenditure in 2013 and 2018. The minimum household consumption expenditure in 2018 exceeded than that in 2013. Comparing the average (CA) value and the difference between minimum household expenditures in the two years on all groups in general, and on food, beverages, health, and education in specific shows that the financial support the Citizen Account provides, indeed covers financial burdens that the low-income individuals would bear due to increase in prices.